Introducing the Expectations and Preference Scales for Couple Therapy (EPSCT): Development, Psychometric Evaluation, and Suggested Use in Practice and Research. Issue 4 (28th March 2019) - Friedlander, Myrna L.; Muetzelfeld, Hannah; Re, Silvia; Colvin, Kimberly F.; Quinn‐Nilas, Christopher; Smoliak, Olga
Abstract : While it is known that client factors account for the largest proportion of outcome variance across treatment modalities, little is known about how clients' characteristics affect the process and effectiveness of couple therapy. To further knowledge in this area, we created a brief, practice‐friendly measure, the Expectation and Preference Scales for Couple Therapy (EPSCT). Three self‐report scales assess clients' Outcome expectations (e.g., I expect our relationship to improve as a result of couple therapy ) and role expectations for Self (e.g., I expect to listen to my partner's concerns ) and Partner (e.g., I expect my partner to blame me ). Three Cognitive‐Behavioral, Emotionally Focused, and Family Systems preference scales use a forced‐choice format to measure the comparative strength of respondents' preferences for interventions broadly reflective of each approach. A large item pool was developed from relevant literature and clinical experience and refined based on face and content analyses with two panels of experienced couple therapists and researchers. Across four studies with 1, 175 participants, the scales' internal consistency reliabilities were similar and their construct validity was supported with confirmatory factor analyses and significant correlations with several established measures, including expectation measures developed for individual psychotherapy and measures of attitudes toward professional help seeking and valuing personal growth. Across all studies, participants had stronger role expectations for themselves than their partners, although gender effects differed by sample. We discuss how to use the 15‐item EPSCT in clinical practice and in future research as a predictor of couple therapy processes and outcomes. Abstract : Aunque se sabe que los factores de los clientes representan la mayor parte de la variación en los resultados a través de las modalidades de tratamiento diversas, no se sabe mucho acerca de cómo las características de los clientes afectan el proceso y efectividad de la terapia de pareja. Para avanzar el conocimiento en este campo, hemos creado una breve medida favorable a la práctica, las Escalas de expectativas y preferencias para terapia de pareja (EPSCT en inglés). Tres escalas de autoinforme evalúan las expectativas de resultados de los clientes (p.ej. Espero que nuestra relación mejore como resultado de la terapia de pareja ) y las expectativas de roles para sí mismo (p.ej. Espero escuchar las preocupaciones de mi pareja ) y para la pareja (p.ej. Espero que mi pareja me culpe ). Tres escalas de preferencias cognitivo‐conductiva, enfocada en emociones y de sistemas familiares emplean un formato de elección forzada para medir la fortaleza comparativa de las preferencias de los interrogados por intervenciones que reflejan cada enfoque a grandes rasgos. Se elaboró un conjunto amplio de ítems a partir de la literatura y experiencia clínica pertinentes y se refinó a base de análisis de apariencia y contenido con dos paneles de terapistas de pareja e investigadores experimentados. En la totalidad de cuatro estudios con 1175 participantes, las fiabilidades de coherencias internas fueron similares y su validez de constructo fue respaldada por análisis factoriales confirmatorios y correlaciones significativas con varias medidas ya establecidas, incluyendo medidas de expectativas desarrolladas para psicoterapias individuales y medidas de actitudes hacia la búsqueda de ayuda profesional y la valoración del crecimiento personal. En todos los estudios, los participantes mostraron expectativas de roles más fuertes para sí mismos que para sus parejas, aunque hubo diferencias en los efectos de género por muestra. Discutimos cómo usar el EPSCT con sus 15 ítems en la práctica clínica e investigaciones futuras como predictor de procesos y resultados de la terapia de pareja. Abstract : 众所周知, 不同的治疗方法造成有差异的治疗结果很大程度的原因来自于受诊者, 但是人们对于受诊疗的个体的差别到底如何影响了伴侣治疗的过程和有效性却知之甚少。为了增进对这方面的了解, 我们编制了一个比较简洁的, 使用友好的量表, 伴侣治疗期待和偏好程度量表(EPSCT)。三个自测的量表用来测试受诊者结果预期(例如, 我期待我们的关系在伴侣治疗后得到改善), 对自我的角色期待(例如我期望倾听到对方的想法)和伴侣角色期待(例如我希望对方批评我。)偏好量表有三个种类即认知‐行为的, 专注情感的, 和家庭系统的。研究中要求被测者必须作出选择, 从而可以测量她们对于不同的介入方法的比较之后得出的偏好程度。很多选项都来自现有相关的文献和临床诊疗经验, 并在和两组经验丰富的伴侣治疗师和研究者的讨论和内容分析之后提炼而成。在4项研究中, 合起来有1175位参与者测试, 结果表明这些量表的内部一致性和信度相似, 结构效度也受验证性因子分析的支持, 和几个已有的量表有很大的相关性。比如为个体心理治疗的期待量表, 寻求专业帮助和注重个人成长的态度量表等。在所有的研究中, 受试者对自身的角色期待要强于对对方的, 不同的样本中性别的影响程度有差异。文中讨论了如何在实践中使用 15个项目的EPSCT和在未来的研究中如何可以用作伴侣治疗过程与结果的一个预测工具。